Estimation of potential growth rate (with application to USA, Europe and East Asia) - Klein, Laurence R. (SPOUDAI Journal of Economics and Business, 1999)
This article is revised draft of the lecture given at the University of Piraeus on June 7th 1999, on the occasion of granting Professor Klein a honorary Doctorate degree by the department of Economics.